2017
DOI: 10.1039/c7an00660h
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring multiple signals along with the reaction time: improving recognition capability of a multidimensional colorimetric sensor array for sensitive protein detection

Abstract: The development of sensitive and cheap sensor arrays for identification of proteins plays an important role in many bioanalytical and clinical investigations. Here, we introduce a multidimensional colorimetric sensor array for the detection of multiple proteins based on acquiring multiple signals along with the reaction time to enhance the discrimination ability. In a single experiment, the unique fingerprint for each protein against the sensor array is generated from a response absorbance signal at three reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Thus, such a sensor was able to effectively identify 13 proteins, BSA and HSA mixtures, unknown samples and proteins in urine with an accuracy of 100%. They also developed another triple-channel colorimetric sensor by collecting the absorbance signals at three different reaction time points (10, 15, and 20 min) (Yang et al, 2017 ). Ten proteins in both aqueous solution and human urine were discriminated with 100% accuracy.…”
Section: Multi-wavelength-based Single Sensing System For Protein Recmentioning
confidence: 99%
“…Thus, such a sensor was able to effectively identify 13 proteins, BSA and HSA mixtures, unknown samples and proteins in urine with an accuracy of 100%. They also developed another triple-channel colorimetric sensor by collecting the absorbance signals at three different reaction time points (10, 15, and 20 min) (Yang et al, 2017 ). Ten proteins in both aqueous solution and human urine were discriminated with 100% accuracy.…”
Section: Multi-wavelength-based Single Sensing System For Protein Recmentioning
confidence: 99%
“…For example, Chen et al reported colorimetric sensor arrays based on three nanozymes, namely, graphene oxide, molybdenum disulfide (MoS 2 ) and tungsten disulfide (WS 2 ) as sensing elements for antioxidant detection. 18 As reported, most colorimetric array sensors were constructed using nanomaterials, 19 pH, 20 metal ions, 21,22 fluorescence, 20,23,24 and time 25 as sensing elements. However, there is no report on the colorimetric array based on one nanozyme with the double enzyme-like activities.…”
Section: Introductionmentioning
confidence: 99%
“…However, discrimination of complex mixture is still a great challenge for sensor array-based sensing systems due to the complex responses and intervention of various analytes. For example, although some sensor arrays have achieved pretty high sensitivity and accuracy in detection of single protein samples; few reports have been published on the differentiation between complex protein samples and proteins in biological samples.…”
mentioning
confidence: 99%